Sense of coherence, its components and depressive and anxiety symptoms in expecting women and their partners – A FinnBrain Birth Cohort Study - Sirkiä Carlos; Laakkonen Eero; Nordenswan Elisabeth; Karlsson Linnea; Korja Riikka; Karlsson Hasse; Kataja Eeva-Leena (Elsevier, 2025)
Objective
Expecting mothers with high sense of coherence (SOC) exhibit improved physical, emotional, and childbearing health. However, the dimensions of SOC and the factor structure of the SOC-13 scale during prenatal period is slightly known. Especially the differences in experiencing SOC and its components (comprehensibility, manageability, meaningfulness) among both expecting parents (mothers and fathers) is poorly understood. The association between SOC and mood disorder symptoms (depression and anxiety) during pregnancy is scarcely studied.
Methods
The structure of the SOC-13 scale, differences in SOC experiences, and the associations between SOC and depressive and anxiety symptoms were studied in a sample of 2784 pregnant women (mothers) and 1661 men/partners (fathers) belonging to the FinnBrain Birth Cohort Study. Self-reports (SOC-13, EPDS, SCL-90: ANX) from gestational week 24 were used. Confirmatory factor analysis (CFA) and invariance testing was carried out to investigate the factorial structure of SOC-13 among both groups (mothers and fathers). Group comparisons were used to study differences in the level of SOC among mothers vs. fathers, low vs. high depression and anxiety subgroups, and multiparous vs. nulliparous mothers.
Results
A two-factor model for SOC-13 consisting of comprehensibility-manageability and meaningfulness fitted the data best. Mothers reported higher levels of meaningfulness, whereas fathers reported higher levels of comprehensibility-manageability. SOC was significantly higher among fathers vs. mothers, but mothers with depressive symptoms reported higher SOC than fathers with depressive symptoms.
Conclusions
During pregnancy, SOC can be viewed as a two-dimensional (vs. one- or three-dimensional) concept, and mothers and fathers have differences in the components of SOC. Importantly, mothers vs. fathers with depressive symptoms express higher overall SOC indicating that pregnancy may relate to higher than usual SOC especially among women with psychological distress. Understanding how expecting mothers and fathers experience SOC during pregnancy, particularly in relation to depressive symptoms, helps midwives and maternity care providers to focus health promoting support more precisely.